Lithium ferric fluorosulfate positive electrode material as well as preparation method and application thereof
By covering the carbon nanotuba on the illegal iver material of fluorosate, the problem of insufficient electronic conductivity and ionic electrical conductivity of the electronic conductivity and cycle are solved.
Patent Information
- Application Number
- CN202411440624.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-15
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-10-15
AI Technical Summary
The existing lithium foxosulfate positive electrode materials have poor electronic conductivity and ionic conductivity, resulting in the inability to further improve the specific capacity and cycling performance, and the preparation method is complicated and the cost is high.
By covering the carbon nanotuba on the lithium fluorosate, and controlling the particle size of the granular and secondary particles of the positive electrode material, it significantly improves its electronic conductivity and ionic conductivity.
A significant improvement of the comparison capacity and cycle performance of the lithium of iron sulfate lithium, and excellent high temperature and low temperature performance, simple preparation methods, and low cost.
Smart Images

Figure CN119361688A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium batteries, and in particular to a lithium iron fluorosulfate positive electrode material and a preparation method and application thereof. Background Art
[0002] With the rapid development of the world economy, the demand for energy in countries around the world is growing. The global energy shortage has become a topic of concern, and finding renewable clean green energy has become the most urgent task at present. As a type of green and environmentally friendly renewable resource, lithium-ion batteries have the advantages of large capacity and high energy density, and are considered to be the most promising secondary batteries.
[0003] Among the positive electrode materials for lithium-ion batteries, polyanion-type positive electrode materials for lithium-ion batteries have an open three-dimensional framework structure. The volume change of the material is small during the process of lithium ion extraction / embedding, so it has good cycle stability. As a new type of polyanion-type positive electrode material for lithium-ion batteries, lithium ferric fluorosulfate LiFeSO4F has two major advantages over traditional LiFePO4 (LFP) as a positive electrode material for lithium-ion batteries: (1) the material has a higher working voltage (3.6V); (2) the material has a higher ionic conductivity. Lithium ferric fluorosulfate has two crystal forms, tavorite monoclinic form and triplite triclinic form. The monoclinic form has a working voltage of 3.6V, which is lower, but it has higher ionic conductivity and higher discharge specific capacity. The triclinic form has a working voltage of 3.9V, which is higher, and it has higher energy density, but lower discharge specific capacity.
[0004] For lithium iron fluorosulfate positive electrode materials, the most commonly used synthesis method is the solvothermal method. U.S. Patent US 9,216,912B2, Korean Patent KR20160112340A, and Chinese Patent CN105668643A all mention the solvothermal preparation method of LiFeSO4F material with tavorite monoclinic structure. However, this method has complicated procedures and high costs. The electronic conductivity of the prepared material is poor, resulting in the inability to further improve the specific capacity and cycle performance of the material, which seriously restricts the application of LiFeSO4F as an electrode material.
[0005] How to further improve the electronic conductivity and ionic conductivity of LiFeSO4F so that it has a higher specific capacity and better cycle performance while keeping the production cost low is a difficulty in the LiFeSO4F field. Summary of the invention
[0006] In view of the shortcomings and deficiencies of the prior art, the present invention provides an improved lithium iron fluorosulfate positive electrode material, which has better electronic conductivity and ionic conductivity, higher specific capacity and more excellent cycle performance, and excellent high temperature performance and low temperature performance.
[0007] To achieve the above object, the technical solution adopted by the present invention is as follows:
[0008] A lithium ferrous fluorosulfate positive electrode material, comprising lithium ferrous fluorosulfate and carbon nanotubes coated on the lithium ferrous fluorosulfate, and the positive electrode material is a secondary particle, the particle size of the secondary particle is 2 to 10 μm; the secondary particle is composed of nanometer-scale primary particles; the particle size of the primary particles is 20 to 200 nm.
[0009] In the prior art, the specific capacity and cycle performance of lithium iron fluorosulfate cathode materials are not enough, and usually the preparation methods thereof, such as the solvothermal method, are complex and costly. The present invention can significantly improve its electronic conductivity and ionic conductivity by coating carbon nanotubes on lithium iron fluorosulfate and controlling the primary particle size and secondary particle size of the cathode material, so that the cathode material has a higher specific capacity and a more excellent cycle performance, and both high temperature performance and low temperature performance are excellent. After the surface is coated with carbon nanotubes, the electronic conductivity of the material is improved, and lithium ion channels are also constructed to further improve the ionic conductivity of the material, thereby achieving the improvement of the ionic conductivity and electronic conductivity of the lithium iron fluorosulfate material, which can block the side reaction of the electrolyte when used in lithium ion batteries, and ensure the cycle stability of the cathode material when used in lithium ion batteries.
[0010] In some embodiments, the mass of the carbon nanotubes accounts for 2% to 12% of the mass of the positive electrode material.
[0011] In some embodiments, the carbon nanotubes are selected from single-walled carbon nanotubes or multi-walled carbon nanotubes.
[0012] In some embodiments, the carbon nanotubes have an outer diameter of 10 to 90 nm, an inner diameter of 1 to 5 nm, an interlayer distance of 0.3 to 0.4 nm, and a length of 10 to 100 μm.
[0013] In some embodiments, the chemical formula of lithium iron fluorosulfate is Li x FeSO4F x , wherein x is 1.02 to 1.10, and x is preferably 1.02 to 1.06.
[0014] In some embodiments, the lithium ferrous fluorosulfate includes a tavorite monoclinic crystal and a triplite triclinic crystal, and a molar ratio of the monoclinic crystal to the triclinic crystal is 25:1 to 65:1.
[0015] In some embodiments, the positive electrode material is prepared by a preparation method comprising the following steps: 1) grinding lithium fluoride to a particle size of less than 10 μm; 2) ball-milling the ground lithium fluoride, ferrous sulfate, and carbon nanotubes to obtain a mixture; 3) calcining the mixture to obtain the lithium ferrous sulfate fluoride positive electrode material.
[0016] The present invention grinds lithium fluoride to a specific small particle size, then ball-mills it with other precursors such as ferrous sulfate and a modifier carbon nanotube, mixes them evenly, and then performs calcination and solid-phase reaction, so that a positive electrode material with controllable particle size can be obtained, and the charge-discharge performance and cycle performance of the positive electrode material are improved.
[0017] In some embodiments, the cathode material has a discharge capacity of 120 mAh at 25°C and 0.1C. · g -1 The capacity retention rate after 200 cycles at 25°C and 1C is more than 75%, and the discharge capacity at 0°C and 0.1C is 120mAh. · g -1 The positive electrode material of the present invention has better electronic conductivity and ionic conductivity, higher specific capacity and better cycle performance, and excellent low temperature performance.
[0018] In some embodiments, the cathode material has a discharge capacity of 135 mAh at 25°C and 0.1C. · g -1 The capacity retention rate after 200 cycles at 25°C and 1C is more than 95%, and the discharge capacity at 0°C and 0.1C is 135mAh. · g -1 The positive electrode material of the present invention has better electronic conductivity and ionic conductivity, higher specific capacity and better cycle performance, and excellent low temperature performance.
[0019] The present invention also provides a method for preparing the aforementioned lithium ferrous fluorosulfate positive electrode material, the preparation method comprising the following steps: 1) grinding lithium fluoride to a particle size of less than 10 μm; 2) ball-milling and mixing the ground lithium fluoride, ferrous sulfate, and carbon nanotubes to obtain a mixture; 3) calcining the mixture to obtain the lithium ferrous fluorosulfate positive electrode material.
[0020] In some embodiments, in step 1), lithium fluoride is ground to a particle size of 5-10 μm.
[0021] In some embodiments, in step 1), lithium fluoride is ground by ball milling.
[0022] Preferably, the rotation speed of the ball mill is 300-500 r / min.
[0023] Preferably, the ball milling time is 12 to 24 hours.
[0024] In some embodiments, the ferrous sulfate is ferrous sulfate monohydrate.
[0025] In some embodiments, the molar ratio of lithium fluoride to ferrous sulfate after grinding is 1.05-1.15:1.
[0026] In some embodiments, in step 2), the ball milling is performed in a planetary ball mill.
[0027] In some embodiments, in step 2), the rotation speed of the ball mill is 300-500 r / min.
[0028] In some embodiments, in step 2), the ball milling time is 15 to 60 minutes.
[0029] In some embodiments, the calcination temperature is 290-340° C., preferably 290-310° C. When the calcination temperature is too high, the monoclinic crystal in lithium iron fluorosulfate will transform into a triclinic crystal, which will reduce the discharge specific capacity of the positive electrode material.
[0030] In some embodiments, the calcination is performed in an atmosphere of inert gas; and the calcination time is 20 to 28 hours.
[0031] In some embodiments, the preparation method further comprises a step of screening after calcining.
[0032] In some embodiments, the mesh size of the sieve used for sieving is 200-600 meshes, preferably 300-500 meshes, and more preferably 400 meshes.
[0033] The present invention also provides a use of the above-mentioned lithium iron fluorosulfate positive electrode material in a lithium ion battery.
[0034] The present invention also provides a lithium-ion battery, which comprises a positive electrode material, a negative electrode material and a separator, wherein the positive electrode material comprises the above-mentioned lithium ferrous sulfate positive electrode material.
[0035] Compared with the prior art, the present invention has the following advantages:
[0036] The positive electrode material of the present invention is a polyanion positive electrode material. The surface of the lithium ferric fluorosulfate material is coated with carbon nanotubes, and the carbon nanotubes are evenly distributed and interspersed on the lithium ferric fluorosulfate. After the surface is coated with carbon nanotubes, the ionic conductivity and electronic conductivity of the lithium ferric fluorosulfate material can be further improved. When used in a lithium ion battery, the side reaction of the electrolyte can be blocked, thereby ensuring the cycle stability of the positive electrode material when used in a lithium ion battery. The cycle stability of the positive electrode material of the present invention is greatly improved compared with the prior art.
[0037] The lithium ion battery positive electrode material of the present invention has very excellent specific capacity and cycle performance, and also has excellent low-temperature performance, and its preparation method is simple in process, low in cost, and good in repeatability. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1 This is the SEM image of the positive electrode material obtained in Example 1.
[0039] Figure 2 This is the SEM image of the positive electrode material obtained in Comparative Example 1.
[0040] Figure 3 This is the XRD pattern of the positive electrode material obtained in Example 1.
[0041] Figure 4 This is the XRD diagram of the positive electrode material obtained in Comparative Example 1.
[0042] Figure 5 It is a graph showing the first charge and discharge curves of the positive electrode materials of lithium-ion batteries assembled in the corresponding embodiments and comparative examples at 25°C and 0.1C.
[0043] Figure 6 It is a cycle test curve diagram of the lithium-ion battery positive electrode materials assembled in the corresponding embodiments and comparative examples at 25°C and 1C.
[0044] Figure 7 This is a cycle test curve diagram of the lithium-ion battery positive electrode material assembled in Example 1 at 25°C, 1C and 5C.
[0045] Figure 8 The 0.1C first charge and discharge curves of the lithium-ion battery positive electrode material assembled in Example 1 at different temperatures, where normal temperature is room temperature 25°C.
[0046] Fig. 9 It is a 0.1C first charge and discharge curve diagram of the lithium-ion battery positive electrode material (LFSF) assembled in Example 1 and the commercial lithium iron phosphate (LFP) positive electrode material at 0°C.
[0047] Fig.101C cycle test curve of the lithium-ion battery positive electrode material (LFSF) assembled in Example 1 and the commercial lithium iron phosphate (LFP) positive electrode material at 0°C. DETAILED DESCRIPTION
[0048] The technical solution of the present invention is described in detail below in conjunction with specific embodiments so that those skilled in the art can better understand and implement the technical solution of the present invention, but the present invention is not limited to the scope of the examples.
[0049] Example 1
[0050] This embodiment provides a lithium iron fluoride sulfate positive electrode material, and the preparation method thereof is as follows:
[0051] 1) Weigh a certain amount of lithium fluoride, pour it into a ball mill, cover the ball mill tightly, seal it, clamp it on a planetary ball mill, and mill it at a speed of 400 r / min for 16 hours to obtain lithium fluoride with a particle size of 5 μm for standby use.
[0052] 2) Weigh ferrous sulfate monohydrate and the above-mentioned ball-milled lithium fluoride to a molar ratio of 1:1.1, and then add multi-walled carbon nanotubes (outer diameter of 20nm, inner diameter of 2nm, interlayer distance of 0.3nm, length of 25μm) to obtain a mixture, in which the mass fraction of multi-walled carbon nanotubes is 5%. Pour the mixture into a ball mill, briefly mix, cover the ball mill tightly, seal it, clamp it on a planetary ball mill, and mill it at a speed of 450r / min for 30 minutes.
[0053] 3) The ball-milled mixture was placed in a tube furnace for calcination at a heating rate of 5° C. / min, a calcination temperature of 300° C., an argon atmosphere, and a calcination time of 24 hours.
[0054] 4) After calcination, cool naturally to room temperature and pass through a 400-mesh sieve to obtain the positive electrode material, which has the general formula of Li 1.019 FeSO4F 1.019 . Figure 1 The SEM image of the obtained positive electrode material shows that the secondary particles are 5 μm in size and are composed of nano-sized primary particles; the particle size of the primary particles is 60 nm. Figure 3 The XRD diagram of the obtained positive electrode material is shown in FIG. 1. In the material, the lithium iron fluorosulfate includes a tavorite monoclinic crystal and a triplite triclinic crystal, and the molar ratio of the monoclinic crystal to the triclinic crystal is 65:1.
[0055] Example 2
[0056] This embodiment provides a lithium iron fluorosulfate positive electrode material, and its preparation method is basically the same as that of embodiment 1, except that the calcination temperature is replaced with 320° C. The general formula and crystal molar ratio of the obtained positive electrode material are shown in Table 1 below.
[0057] Example 3
[0058] This embodiment provides a lithium iron fluorosulfate positive electrode material, and its preparation method is basically the same as that of Example 1, except that the multi-walled carbon nanotubes are replaced with single-walled carbon nanotubes (outer diameter of 40 nm, inner diameter of 4 nm, interlayer distance of 0.3 nm, and length of 40 μm). The general formula and crystal molar ratio of the obtained positive electrode material are shown in Table 1 below.
[0059] Example 4
[0060] This embodiment provides a lithium iron fluorosulfate cathode material, and its preparation method is basically the same as that of embodiment 1, except that the mass fraction of multi-walled carbon nanotubes is replaced by 10%. The general formula and crystal molar ratio of the cathode material obtained are shown in Table 1 below.
[0061] Example 5
[0062] This embodiment provides a lithium iron fluoride sulfate cathode material, and its preparation method is basically the same as that of embodiment 1, except that the particle size of the ground lithium fluoride is adjusted to 10 μm. The general formula and crystal molar ratio of the cathode material are shown in Table 1 below.
[0063] Example 6
[0064] This embodiment provides a lithium iron fluoride sulfate cathode material, and its preparation method is basically the same as that of embodiment 1, except that the molar ratio of ferrous sulfate monohydrate to ball-milled lithium fluoride is adjusted to 1:1.05. The general formula and crystal molar ratio of the obtained cathode material are shown in Table 1 below.
[0065] Comparative Example 1
[0066] This comparative example provides a lithium iron fluoride sulfate positive electrode material, and its preparation method is basically the same as that of Example 1, except that: multi-walled carbon nanotubes are not added to the mixture. Figure 2 is the SEM image of the obtained positive electrode material. Figure 4 : is the XRD graph of the obtained positive electrode material. Compared with the SEM graph of Example 1, it can be found that the positive electrode material of Example 1 has a uniform carbon coating layer of multi-walled carbon nanotubes. Compared with the XRD graph of Example 1, it can be seen that the carbon coating layer of the multi-walled carbon nanotubes of Example 1 does not change the actual material composition of lithium iron fluorosulfate.
[0067] Comparative Example 2
[0068] This comparative example provides a lithium iron fluoride sulfate positive electrode material, and its preparation method is basically the same as that of Example 1, except that step 1) is not performed, that is, the lithium fluoride is not ball-milled in advance. It is found that the obtained positive electrode material is easily agglomerated when dispersed in N,N'-methylpyrrolidone, resulting in a decrease in the specific capacity and cycle performance of the assembled button battery.
[0069] Comparative Example 3
[0070] This comparative example provides a lithium iron fluoride sulfate positive electrode material, and its preparation method is basically the same as that of Example 1, except that the ball milling in step 2) is replaced by manual grinding. It is found that the ferrous sulfate monohydrate and lithium fluoride are not mixed uniformly, resulting in a significant decrease in the specific capacity of the assembled button battery.
[0071] Comparative Example 4
[0072] This comparative example provides a lithium iron fluorosulfate positive electrode material, and its preparation method is basically the same as that of Example 1, except that the calcination temperature is replaced with 350° C. It is found that during the calcination process, a large amount of triclinic lithium iron fluorosulfate is generated, resulting in a decrease in the discharge specific capacity of the assembled button battery.
[0073] Comparative Example 5
[0074] This comparative example provides a lithium iron fluoride sulfate positive electrode material, and its preparation method is basically the same as that of Example 1, except that the molar ratio of ferrous sulfate monohydrate to lithium fluoride after ball milling is adjusted to 1:1. It is found that due to the loss of lithium fluoride during the ball milling process and the roasting process, the solid phase reaction is not completely carried out under the feeding, which ultimately leads to a decrease in the specific capacity of the assembled button battery and a deterioration in the cycle performance.
[0075] Comparative Example 6
[0076] This comparative example provides a lithium iron fluorosulfate positive electrode material, and its preparation method is basically the same as that of Example 1, except that the multi-walled carbon nanotubes are replaced by SP conductive carbon black.
[0077] Comparative Example 7
[0078] This comparative example provides a lithium iron fluorosulfate positive electrode material, and its preparation method is basically the same as that of Example 1, except that the multi-walled carbon nanotubes are replaced by KB Ketjen Black.
[0079] Performance test: At the test temperature, weigh 0.27g of the positive electrode material of each embodiment and comparative example, add 0.015g of conductive carbon black and 0.015g of polyvinylidene fluoride, and then evenly disperse in N,N'-methylpyrrolidone. After mixing evenly, coat it on aluminum foil to make an electrode sheet. In an argon atmosphere glove box, use a metal lithium sheet as the counter electrode, 16μm polyethylene as the diaphragm, and 1MLiPF6EMC:FEC (3:1V) + 0.05M LiDFOB as the electrolyte to assemble a button cell. The battery was charged and discharged within the voltage range of 2.5-4.5V. The results are shown in Table 1 below. Composition chemical formula Li x FeSO4F x The test method of Zhongx is as follows: ICP inductively coupled plasma is used for testing. High-temperature plasma is used to ionize the atoms in the final product, and the specific spectral lines emitted or absorbed by these ions are measured to quantitatively analyze the content of Li and Fe. After the final product is ionized in the plasma, the atoms or ions will emit characteristic spectra. Qualitative and quantitative analysis is performed based on the characteristic spectral lines of Li and Fe.
[0080] Table 1
[0081]
[0082] From the comparison between Example 1 and Comparative Example 1, it can be seen that the button cell assembled from pure lithium iron fluoride sulfate cathode material (not coated with carbon nanotubes) has poor electrochemical performance, extremely low specific capacity, and extremely poor cycle performance. However, after Example 1 is coated with carbon nanotubes, both the specific capacity and cycle performance are significantly improved.
[0083] From the comparison between Example 1 and Comparative Example 2, it can be seen that if lithium fluoride is not ball-milled in advance, the electrochemical performance of the button battery assembled from the final product will decrease and the cycle performance will deteriorate. However, after lithium fluoride is ball-milled in advance in Example 1, the specific capacity and cycle performance are significantly improved.
[0084] From the comparison between Example 1 and Comparative Example 3, it can be seen that if the ball mill is changed to hand mill, the cycle performance of the button battery assembled from the final product is extremely poor. However, after ball milling, the cycle performance of Example 1 is significantly improved.
[0085] From the comparison between Example 1 and Comparative Example 4, it can be seen that if the calcination temperature is too high, more triplite phases will be generated, resulting in a decrease in the specific capacity and cycle performance of the button battery assembled from the final product. When the calcination temperature of the present invention is adopted, a very small amount of triplite phases will be generated, and the specific capacity and cycle performance will be significantly improved.
[0086] From the comparison between Example 1 and Comparative Example 6, it can be seen that if the carbon nanotubes are replaced with conductive carbon black, the specific capacity and rate performance of the button battery assembled from the final product are extremely poor. However, after Example 1 is coated with carbon nanotubes, the specific capacity and rate performance are significantly improved.
[0087] From the comparison between Example 1 and Comparative Example 7, it can be seen that if the carbon nanotubes are replaced with Ketjen black, the specific capacity and cycle performance of the button battery assembled from the final product are both reduced. However, after Example 1 is coated with carbon nanotubes, the specific capacity and cycle performance are significantly improved.
[0088] At 0°C, the above method was used to test the electrical properties of the positive electrode material of Example 1 and commercial lithium iron phosphate (LFP), as shown in Table 2 below. It can be seen that the electrochemical performance of the material of Example 1 at low temperature is significantly better than that of traditional LFP.
[0089] Table 2
[0090]
[0091] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with the technology to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.
[0092] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
Claims
1. A lithium iron fluoride sulfate positive electrode material, characterized in that: The positive electrode material comprises lithium ferrous sulfate and carbon nanotubes coated on the lithium ferrous sulfate, and the positive electrode material is secondary particles, the particle size of the secondary particles is 2 to 10 μm; the secondary particles are composed of nanometer-level primary particles; the particle size of the primary particles is 20 to 200 nm.
2. The lithium iron fluorosulfate positive electrode material according to claim 1, characterized in that: The mass of the carbon nanotubes accounts for 2% to 12% of the mass of the positive electrode material; and / or the carbon nanotubes are selected from single-walled carbon nanotubes or multi-walled carbon nanotubes; and / or the carbon nanotubes have an outer diameter of 10 to 90 nm, an inner diameter of 1 to 5 nm, an interlayer spacing of 0.3 to 0.4 nm, and a length of 10 to 100 μm.
3. The lithium iron fluorosulfate positive electrode material according to claim 1, characterized in that: The general chemical formula of the lithium iron fluorosulfate is Li x FeSO4F x , wherein x is 1.02 to 1.10; and / or, the lithium ferrous sulfate comprises a tavorite monoclinic crystal and a triplite triclinic crystal, and the molar ratio of the monoclinic crystal to the triclinic crystal is 25:1 to 65:
1.
4. The lithium iron fluorosulfate positive electrode material according to claim 1, characterized in that: The positive electrode material is prepared by a preparation method comprising the following steps: 1) grinding lithium fluoride to a particle size of less than 10 μm; 2) ball-milling and mixing the ground lithium fluoride, ferrous sulfate and carbon nanotubes to obtain a mixture; 3) calcining the mixture to obtain the lithium ferrous sulfate fluoride positive electrode material.
5. The lithium iron fluorosulfate positive electrode material according to claim 1, characterized in that: The positive electrode material has a discharge specific capacity of 120 mAh at 25°C and 0.1C. · g -1 The capacity retention rate after 200 cycles at 25°C and 1C is more than 75%, and the discharge capacity at 0°C and 0.1C is 120mAh. · g -1 above.
6. A method for preparing the lithium iron fluorosulfate positive electrode material according to any one of claims 1 to 5, characterized in that: The preparation method comprises the following steps: 1) grinding lithium fluoride to a particle size of less than 10 μm; 2) ball-milling the ground lithium fluoride, ferrous sulfate and carbon nanotubes to obtain a mixture; 3) calcining the mixture to obtain the lithium ferrous sulfate cathode material.
7. The method for preparing the lithium iron fluorosulfate positive electrode material according to claim 6, characterized in that: In step 1), the lithium fluoride is ground to a particle size of 5-10 μm; and / or, in step 1), the lithium fluoride is ground by ball milling; preferably, the rotation speed of the ball mill is 300-500 r / min; and / or, the ball milling time is 12-24 h.
8. The method for preparing the lithium iron fluorosulfate positive electrode material according to claim 6, characterized in that: The ferrous sulfate is ferrous sulfate monohydrate; and / or the molar ratio of the ground lithium fluoride to ferrous sulfate is 1.05-1.15:
1.
9. The method for preparing the lithium iron fluorosulfate positive electrode material according to claim 6, characterized in that: In step 2), the ball milling is carried out in a planetary ball mill; and / or, in step 2), the rotation speed of the ball milling is 300 to 500 r / min; and / or, in step 2), the ball milling time is 15 to 60 min.
10. The method for preparing the lithium iron fluorosulfate positive electrode material according to claim 6, characterized in that: The calcination temperature is 290-340° C., preferably 290-310° C., and / or the calcination is carried out in an inert gas atmosphere, the calcination time is 20-28 hours, and / or the preparation method further comprises a screening step after the calcination.
11. Use of the lithium iron fluorosulfate positive electrode material according to any one of claims 1 to 5 in lithium ion batteries.
Citation Information
Patent Citations
Method for preparing lithium ion batteries cathode material
CN105668643A
Preparation method of cathode active material for lithium rechargeable battery and cathode active material for lithium rechargeable battery using the same
KR1020160112340A
Method for preparing alkali metal and transition metal fluorosulfates
US9216912B2
Fluorinated ferric sulfate salt compound as well as preparation method and application thereof
CN102332580A
Anode material for lithium ion battery and preparation method of anode material
CN103887493A
Cited By
Lithium iron fluorosulfate positive electrode material, preparation method therefor, and use thereof
WO2026082001A1